2008
DOI: 10.1111/j.1540-8191.2007.00485.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia at 10°C Reduces Neurologic Injury After Hypothermic Circulatory Arrest in the Pig

Abstract: This data support that cerebral protection may be better at very cold temperatures compared to 18 degrees C hypothermia. Regions selectively vulnerable to neuronal injury are offered more neural protection by profound hypothermia. These affects are observed in the acute state, suggesting activation of the apoptotic mechanisms at early stages can be inhibited by profound hypothermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…We have found that profound hypothermia at 10°C during HCA resulted in a significant reduction in neurological injury in selectively vulnerable brain regions. TUNEL (+) staining was significantly less at 10°C in the motor and sensory cortex and the hippocampus compared to 18°C HCA, indicating that there was increased cerebral protection (Ananiadou et al, 2008). These findings are compatible with previous reports that profound hypothermia results in a superior neurological outcome compared to conventional HCA methods.…”
Section: Profound Hpothermia Rduces Aoptotic Nurologic Ijury Ater Hcasupporting
confidence: 82%
See 1 more Smart Citation
“…We have found that profound hypothermia at 10°C during HCA resulted in a significant reduction in neurological injury in selectively vulnerable brain regions. TUNEL (+) staining was significantly less at 10°C in the motor and sensory cortex and the hippocampus compared to 18°C HCA, indicating that there was increased cerebral protection (Ananiadou et al, 2008). These findings are compatible with previous reports that profound hypothermia results in a superior neurological outcome compared to conventional HCA methods.…”
Section: Profound Hpothermia Rduces Aoptotic Nurologic Ijury Ater Hcasupporting
confidence: 82%
“…Bcl-2 is persistently expressed in neurons that survive in ischemia. The sensory cortex is selectively vulnerable to neurologic injury and showed high levels of Bcl-2 expression after HCA at 18°C compared (Ananiadou et al, 2008). Moreover, profound hypothermia at 10°C resulted in a significant decrease in TUNEL(+) staining in this brain region.…”
Section: The Decision Phase For Apoptotic Nerve Cell Death: Evidence mentioning
confidence: 95%
“…18 The idea that lower temperature during prolonged HCA is more neuroprotective derives from experimental studies that show more complete suppression of metabolism and electrophysiological activity at more profound levels of hypothermia, better functional recovery in survival models, and fewer conventional histological changes in the brain 17 . Our experimental findings have shown that profound hypothermia to 10°C reduced neurological injury during 75 min of HCA in an acute porcine model compared to less profoundly cooled (18°C) animals 21,22 . These data support the general consensus that deliberate hypothermia appears to be a reliable method of neuroprotection against injuries related to cerebral ischemia from any cause.…”
Section: Discussionmentioning
confidence: 89%
“…Despite the apparent deleterious effects of prolonged exposure to CPB on brain function and structure, neuroprotective strategies remain an issue of debate [17][18][19][20][21][22][23] . This is related in part to the gap between the experimental understanding of pathophysiological mechanisms underlying brain injury and the clinical application of various neuroprotective strategies.…”
Section: Introductionmentioning
confidence: 99%
“…As such, discovering means to protect the brain during cardiovascular surgery has been the source of focused research. [1][2][3][4][5][6][7] The use of both cardiopulmonary bypass and circulatory arrest have become important means for allowing complex operations on the aorta and brain, and as a means of achieving improved protection of the vulnerable brain. In turn, hypothermic circulatory arrest, which entails cooling the body almost to the point to where it remains in a state of hibernation, has been found to provide the added protection from hypothermia.…”
Section: Introductionmentioning
confidence: 99%